Post-exercise Hot Water Immersion Elicits Heat Acclimation Adaptations in Endurance Trained and Recreationally Active Individuals - Zurawlew, Michael J.; Mee, Jessica A.; Walsh, Neil P. (Frontiers in Physiology, 2018)
Hot water immersion (HWI) after exercise on 6 consecutive days in temperate conditions has been shown to provide heat acclimation adaptations in a recreationally active population. Endurance athletes experience frequent, sustained elevations in body temperature during training and competition; as a consequence, endurance athletes are considered to be partially heat acclimatized. It is therefore important to understand the extent to which endurance trained individuals may benefit from heat acclimation by post-exercise HWI. To this end, we compared the responses of eight endurance trained and eight recreationally active males (habitual weekly endurance exercise: 9 h vs. 3 h) to a 6-day intervention involving a daily treadmill run for 40 min (65% V̇O2 max) in temperate conditions followed immediately by HWI (≤ 40 min, 40°C). Before (PRE) and after the intervention (POST), hallmark heat acclimation adaptations were assessed during a 40-min treadmill run at 65% V̇O2 max in the heat (33°C, 40% RH). The 6 day, post-exercise HWI intervention induced heat acclimation adaptations in both endurance trained and recreationally active individuals. Training status did not significantly influence the magnitude of heat acclimation adaptations from PRE to POST (interactions P > 0.05) for: the reduction in end-exercise rectal core temperature (Tre, mean, endurance trained -0.36°C; recreationally active -0.47°C); the reduction in resting Tre (endurance trained -0.17°C; recreationally active -0.23°C); the reduction in Tre at sweating onset (endurance trained -0.22°C; recreationally active -0.23°C); and, the reduction in mean skin temperature (endurance trained -0.67°C; recreationally active -0.75°C: PRE to POST P < 0.01). Furthermore, training status did not significantly influence the observed reductions in mean V̇O2, mean metabolic energy expenditure, end-exercise physiological strain index, perceived exertion or thermal sensation (PRE to POST P < 0.05). Only end-exercise heart rate was influenced by training status (P < 0.01, interaction); whereby, recreationally active but not endurance trained individuals experienced a significant reduction in end-exercise heart rate from PRE to POST (P < 0.01). In summary, these findings demonstrate that post-exercise hot water immersion presents a practical strategy to reduce thermal strain during exercise-heat-stress in endurance trained and recreationally active individuals.